Urban Epidemic of Dengue Virus Serotype 3 Infection, Senegal, 2009 - Ousmane Faye; Yamar Bâ; Oumar Faye; Cheikh Talla; Diawo Diallo; Rubing Chen; M. Mondo; Rouguiétou Ba; Edgard Macondo; Tidiane Siby; Scott C. Weaver; Mawlouth Diallo; et al. (2014)
An urban epidemic of dengue in Senegal during 2009 affected 196 persons and included 5 cases of dengue hemorrhagic fever and 1 fatal case of dengue shock syndrome. Dengue virus serotype 3 was identified from all patients, and Aedes aegypti mosquitoes were identified as the primary vector of the virus.